INTERDEPENDENCE BETWEEN RETURN AND RISK OF BANKS IN THE REPUBLIC OF SERBIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
In the last two years, the profitability of the banking sector of Serbia has indicated the occasional tendency to recovery. Viewed over the long term, profitability of the banking sector is primarily a function of an increase in lending activities with increased control in the field of credit risk because the credit risk is an essential problem of the banking sector in the Republic of Serbia, the region and individual EU countries. Unlike credit risk, liquidity risk is very insignificant. In this paper, through an approach that has been developed by Alberts, we will explore the correlation between return and risk for a larger group of banks in the Republic of Serbia. Therefore, the main objective of the paper is to determine whether factors such as the size of the bank, i.e. business operations, lending activities, the competitive environment and the style of management of the bank have an impact on the trade-off between return and risk.Keywords: Return on invested funds, capital risk, credit risk, financial leverage